1915 թ. Վանի հերոսամարտը օտար աղբյուրներում - Ռ. Օ. Սահակյան (Հայկական ԽՍՀ գիտությունների ակադեմիա)
Авторы приводимых в статье сообщений (немцы, американцы и др.) были очевидцами жестоких оборонительных боев, которые вели жители города Вана. Все они единогласно утверждают, что турецкие регулярные войска атаковали с намерением уничтожить армянское население города, а армяне только оборонялись.The authors of the information presented in the article (Germans,Americans and others) have been eyewitnesses of the fierce defence battles faught by the inhabitants of Van. All of them insist that a regular Turkish army attacked the Armenian inhabitants of the town intending to annihilate them while the Armenians only defended themselves.
Keywords: History; D History; AMS Armenian Massacres